A Comparative Study of The Effect of Motivating Teachers on Independent Learning Curriculum Implementation on Learning Outcomes of Students - Akhmad Zulkarnain; Ellyna Hafizah; Yudha Irhasyuarna (Journal of Mathematics Science and Computer Education, 2024)
This research aims to (1) Determine whether the learning outcomes of students with motivating teachers are better than those without motivating teachers in junior high schools; (2) Identify the factors that play a role in influencing the learning outcomes of students by motivating and non-motivating teachers. The study involved 37 students from State Junior High School 9 Banjarmasin with motivating teachers and 33 students from State Junior High School 1 Banjarmasin with non-motivating teachers. The results showed (1) The average learning outcomes of students with motivating teachers were 64.59, while the average learning outcomes of students with non-motivating teachers were 78.65. A significant difference was based on the Independent-Samples T-Test One-Tailed with a P-value of 0.000 < 0.05. The research findings indicate that the learning outcomes of students with motivating teachers are not better than those of students with non-motivating teachers; (2) Factors influencing the learning outcomes of students by motivating and non-motivating teachers include the school principal, colleagues, facilities, and infrastructure, learning motivation, teacher's abilities, teacher's leadership, work experience, and the working environment.